Methods of preparing propagules for tropical woody bamboo species - Nieri, Erick Martins; Almeida, Rodolfo Soares de; Melo, lucas Amaral de; Cartolano, Rafael Torres (Scientia Agraria Paranaensis, 2020)
The production of seminal bamboo seedlings is considered not viable, being this the biggest limiting factor. The tissue culture and minicutting are efficient, but very costly techniques, which makes it necessary to search for alternative techniques, such as propagation through culm sections. In this context, the objective of this study was to evaluate the efficiency of three methods of vegetative propagation with segments of the culm of the species Bambusa vulgaris, B. variabilis, B. tuldoides and Dendrocalamus giganteus. The experiment was carried out in a randomized block design, factorial scheme of four (4) species (Bambusa vulgaris, B. variabilis, B. tuldoides and Dendrocalamus giganteus) and three (3) methods of preparing the propagule (a single node, binodal propagule, and binodal propagule + H 2 O), with four replicates and plots of five propagules. The propagules were deposited in shallow pits kept in field conditions. At 45 days, the percentage of shoots was measured and analyzes of variance and Tukey were performed at 5% error probability. For D. giganteus, none of the methods of preparing the propagules proved to be efficient for their propagation. The species B. vulgaris, B. variabilis and B. tuldoides showed higher percentages of sprouting. The method of preparing propagules with a single node was more efficient for B. variabilis, B. vulgaris and B. tuldoides.